Passive acoustic mapping of magnetic microbubbles for cavitation enhancement and localization. (7th January 2015) - Crake, Calum; Victor, Marie de Saint; Owen, Joshua; Coviello, Christian; Collin, Jamie; Coussios, Constantin-C; Stride, Eleanor
Abstract: Magnetic targeting of microbubbles functionalized with superparamagnetic nanoparticles has been demonstrated previously for diagnostic (B-mode) ultrasound imaging and shown to enhance gene delivery in vitro and in vivo . In the present work, passive acoustic mapping (PAM) was used to investigate the potential of magnetic microbubbles for localizing and enhancing cavitation activity under focused ultrasound. Suspensions of magnetic microbubbles consisting of 1, 2-distearoyl-sn-glycero-3-phosphocholine (DSPC), air and 10 nm diameter iron oxide nanoparticles were injected into a tissue mimicking phantom at different flow velocities (from 0 to 50 mm s −1 ) with or without an applied magnetic field. Microbubbles were excited using a 500 kHz single element focused transducer at peak negative focal pressures of 0.1–1.0 MPa, while a 64 channel imaging array passively recorded their acoustic emissions. Magnetic localization of microbubble-induced cavitation activity was successfully achieved and could be resolved using PAM as a shift in the spatial distribution and increases in the intensity and sustainability of cavitation activity under the influence of a magnetic field. Under flow conditions at shear rates of up to 100 s −1 targeting efficacy was maintained. Application of a magnetic field was shown to consistently increase the energy of cavitation emissions by a factor of 2–5 times over the duration of exposures compared to the case without targeting, which was approximately equivalent to doubling the injected microbubble dose. These results suggest that magnetic targeting could be used to localize and increase the concentration of microbubbles and hence cavitation activity for a given systemic dose of microbubbles or ultrasound intensity.